Nesprin-1 role in DNA damage response - Sur, Ilknur (Landes Bioscience, 2014)
Nuclear envelope (NE) proteins have fundamental roles in maintaining nuclear structure, cell signaling, chromatin organization, and gene regulation, and mutations in genes encoding NE components were identified as primary cause of a number of age associated diseases and cancer. Nesprin-1 belongs to a family of multi-isomeric NE proteins that are characterized by spectrin repeats. We analyzed NE components in various tumor cell lines and found that Nesprin-1 levels were strongly reduced associated with alterations in further NE components. By reducing the amounts of Nesprin-1 by RNAi mediated knockdown, we could reproduce those alterations in mouse and human cell lines. In a search for novel Nesprin-1 binding proteins, we identified MSH2 and MSH6, proteins of the DNA damage response pathway, as interactors and found alterations in the corresponding pathways in cells with lower Nesprin-1 levels. We also noticed increased number of γH2AX foci in the absence of exogenous DNA damage as was seen in tumor cells. The levels of phosphorylated kinases Chk1 and 2 were altered in a manner resembling tumor cells and the levels of Ku70 were low and the protein was not recruited to the DNA after hydroxyurea (HU) treatment. Our findings indicate a role for Nesprin-1 in the DNA damage response pathway and propose Nesprin-1 as novel player in tumorigenesis and genome instability.